ANIBACTERIAL EFFICACY AND GAS CHROMATOGRAPHY-MASS SPECTROMETERY ANALYSIS OF BIOACTIVE COMPOUNDS PRESENT IN DIFFERENT EXTRACTS OF ALLIUM SATIVUM - Sharma, Dushyant; Rani, Reena; Chaturvedi, Monika; Yadav, Jaya Parkash (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Medicinal plants are rich libraries containing wide variety of compounds of therapeutic values. Allium sativum commonly known as garlic is a very well-known medicinal plants being used with food products. In the present study, the antibacterial activity of different extracts of A. sativum was investigated along with their phytochemical analysis by gas chromatography-mass spectrometery (GC-MS) to explore antimicrobial compounds present in extracts. Methods: The antibacterial activity of A. sativum was evaluated against 9 reference bacterial strains and 3 MDR bacterial strains including Escherichia coli MDREC1, Klebsiella pneumoniae MDRKP2, and Pseudomonas aeruginosa MDRPA3 by microbroth dilution and agar well diffusion method. Results: The results obtained from agar well diffusion assay showed the zone of inhibition from 12 to 26 mm for different extracts. The methanol and acetone extracts were found most potent against reference and MDR bacterial strains. MIC values were in the range of 1.87â€“7.5 mg/ml. Further, GCMS analysis confirmed the presence of 35 compounds including dodecanoic acid, hexadecanoic acid, and methyl ester in common. Conclusion: The varied antimicrobial activity of extracts was due to the presence of different concentrations of the identified compounds which can be isolated and used for the treatment of various infectious diseases caused by MDR strains of E. coli, P. aeruginosa, and K. pneumoniae.